2022
DOI: 10.5334/tohm.709
|View full text |Cite
|
Sign up to set email alerts
|

Accidental Falls in Patients with Hyperkinetic Movement Disorders: A Systematic Review

Abstract: Background:The significance of falls and their repercussions in Parkinson's disease has been extensively researched. However, despite potentially serious effects on health and quality of life and negative impact on the healthcare system, there is not a sufficient understanding of the role of falls in hyperkinetic movement disorders (HKMDs). This review aims to provide an overview of the prevalence of falls, injuries, and preventive measures in the most common HKMDs.Methods: Studies up to May 1, 2022 were searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 84 publications
(130 reference statements)
0
6
0
Order By: Relevance
“…However, we found that although tDBS significantly reduced tremor in these patients, it had no effect on their inconsistency (Fig. 3C) (22).…”
Section: Motor Inconsistencymentioning
confidence: 84%
See 1 more Smart Citation
“…However, we found that although tDBS significantly reduced tremor in these patients, it had no effect on their inconsistency (Fig. 3C) (22).…”
Section: Motor Inconsistencymentioning
confidence: 84%
“…Additionally, the presence of tremor in the head or trunk (axial tremor) may cause gait instability and increase the risk for falls (19)(20)(21). Indeed, individuals with ET fall twice as much as healthy counterparts (22). Thus, the functional repercussions of tremor are contingent upon its site and intensity, spanning the spectrum from marginal disruption to daily activities and social discomfort to severe outcomes such as occupational impairment or susceptibility to falls and grave injuries.…”
Section: What Are the Functional Implications Of Tremor?mentioning
confidence: 99%
“…Another review on balance and falls in Multiple Sclerosis patients by Cameron et al in the USA reported that 50-80% of these patients have balance and gait dysfunction and more than 50% fall at least once every year [32]. Individuals with neurological disorders have been reported to have more frequent and more severe falls [33].…”
Section: Comorbiditiesmentioning
confidence: 99%
“…[ 2 , 8 ] However, the ataxia score alone cannot fully represent the quality of life (QoL), especially unpredicted falls that significantly affect the QoL. [ 9 12 ]…”
Section: Introductionmentioning
confidence: 99%